Airbnb em Itaipulândia/PR: cocriando valor por meio da infraestrutura de hospedagem alternativa - Oliveira, Nathan Marques (2018)
The sharing economy has generated an impact on the social behavior and business relationships, embracing production and consumption, besides bringing a new vision to topics as sustainability and social well-being. Tourism as a cross-sectoral and intersectoral sector is affected in a comprehensive and total way by this new multiplicity of supply, and it is therefore up to destinations to appropriate tools to aid their development. The objective of this work is to present the steps taken to propose alternative hosting in the destination of Itaipulândia, using the world-wide hosting platform AirBnB, business model of the sharing economy, a movement that favors the access on ownership, and redefines ecosystems of business and personal relationships. The company - and platform - globally connects travelers to hosts through an internet-based platform. AirBnB, as well as other sharing economy businesses, creates relevant and effective value propositions, mediating relationships, engaging and enabling actors to design their ideal service solutions, minimizing objections, and maximizing well-being. Actors become entrepreneurs with collaborative embedded ecosystem culture, benefiting organizations and their collaborative ecosystems, which grow from the continuous effect and result of service experiences. An action research was carried out with the destination community, in order that they will benefit and assist in the process of tourism development of this non-inductive destination, inserting them in the platform and making them part of the increment process of value of Itaipulândia. Finally, this work results in the technological appropriation of the participants involved in the tourist development process of the destination. The importance of this work is based on the powerful tool left as a legacy to those directly involved in the process (local community and public administration); in the consequent improvements throughout the lodging infrastructure chain, thus contributing to regional development.